Efficacy of Probiotics in Children and Adolescents With Atopic Dermatitis: A Randomized, Double-Blind, Placebo-Controlled Study - Andrade, Paula Danielle Santa Maria Albuquerque de; Maria e Silva, Jorgete; Carregaro, Vanessa; Sacramento, Laís Amorim; Roberti, Luciana Rodrigues; Aragon, Davi Casale; Carmona, Fabio; Roxo-Junior, Pérsio (Frontiers in Nutrition, 2022)
Objective To evaluate the clinical efficacy of a mixture of probiotics (Lactobacillus and Bifidobacterium) in children and adolescents with atopic dermatitis (AD) and the effects on sensitization, inflammation, and immunological tolerance. Methods In this double-blind, randomized, placebo-controlled clinical trial, we enrolled 60 patients aged between 6 months and 19 years with mild, moderate, or severe AD, according to the criteria proposed by Hanifin and Rajka. Patients were stratified to receive one gram per day of probiotics or placebo for 6 months. The primary outcome was a decrease in SCORing Atopic Dermatitis (SCORAD). Secondary outcomes were to assess the role of probiotics on the use of topical and oral medicines (standard treatment), serum IgE levels, skin prick test (SPT), and tolerogenic and inflammatory cytokines. Background therapy was maintained. Results Forty patients completed the study (24 probiotics, 16 placebo). After treatment for six months, the clinical response was significantly better in the probiotics group; the SCORAD decreased [mean difference (MD) 27.69 percentage points; 95% confidence interval (CI), 2.44–52.94], even after adjustment for co-variables (MD 32.33 percentage points; 95%CI, 5.52–59.13), especially from the third month of treatment on. The reduction of the SCORAD in probiotic group persisted for three more months after the treatment had been discontinued, even after adjustment for co-variables (MD 14.24 percentage points; 95%CI, 0.78–27.70). Patients in the probiotics group required topical immunosuppressant less frequently at 6 and 9 months. No significant changes were found for IgE levels, SPT and cytokines. Conclusions Children and adolescents with AD presented a significant clinical response after 6 months with a mixture of probiotics (Lactobacillus rhamnosus, Lactobacillus acidophilus, Lactobacillus paracasei, and Bifidobacterium lactis. However, this clinical benefit is related to treatment duration. Probiotics should be considered as an adjuvant treatment for AD.